ANALISIS FAKTOR PUNCAK DAYA TERAS RSG-GAS BERBAHAN BAKAR U3SI2-AL 4,8 GU/CC DENGAN KAWAT KADMIUM - Susiloj, Jati; Pujihastuti, Endiah (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
To upgrade the ability of RSG-GAS core, research about utilization of U3Si2-Al fuel with 4.8 gU/cc density has been done. The using of U3Si2-Al fuel with 4.8 gU/cc density in the RSG-GAS core could increase the operation cycle length from 20 to 29 days. To the reactor can be operated more efficiently. In another side, the effect of high density fuel is the value of control rod reactivity in the one stuck rod condition to be positive caused by increasing core excess reactivity. Those problem has been solved by added cadmium wire at two each side of all the fuel plate. For the RSG-GAS core U3Si2-Al fueled with 4.8 gU/cc density need cadmium wire with minimum diameter about 0.7 mm. Beside excess reactivity, another neutronic parameter that important to observed in the core design in order the fuel damage cannot happen is value of power peaking factor (ppf). Therefore, in this research, the calculation of power factor distribution for RSG-GAS core U3Si2-Al fuel 4,8 gU/cc density with Cd wire has been done by using CITATION module of SRAC code. Calculation result show that the RSG-GAS core U3Si2-Al fuel 4.8 gU/cc density with added cadmium wire at the each side of fuel plate have ppf about 1.2225 .Those value only a little bigger compared with ppf for current RSG-GAS core fueled U3Si2-Al with 2,96 gU/cc density, that is 1.1642. From the analysis of calculation result can concluded that the value of ppf for the RSG-GAS core U3Si2-Al fuel 4.8 gU/cc density with added by cadmium wire was still lower than maximum margin value at the design data in the SAR of the RSG-GAS.